Socio-Economic Ideas of Latin America and the Caribbean in Pakistan: Reception and Re-Elaboration (1965-1980) [Las Ideas Económico-Sociales de América Latina y el Caribe en Pakistán: Recepción y Reelaboración (1965-1980)] - Deves-Valdes, E (2012)
The main objective of this article is to present the reception and re-elaboration of Latin- American social and economic thought in Pakistan. Some authors that have worked with Latin-American ideasare introduced, such as M. A. Mannan and Mahbub ul-Haq, as well as the eidetic context or intellectual environment in which these ideas were received and re-elaborated. First of all, the article defineswhich were the ideas, authors and works considered by the Pakistani authors; secondly, it shows the differences in the ways each Pakistani writer received the ideas of Latin American and Caribbean authors and the ways that Latin American and Caribbean thought was "hybridated" in relation to other eidetic trajectories with the aim of elaborating formulas that would correspond to "ideal types" of hybridations.